2007
DOI: 10.1177/104063870701900419
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Immunoreactivity in Equine Ocular Squamous-Cell Carcinoma

Abstract: Abstract. Squamous-cell carcinoma (SCC) is the second most common tumor in horses, and 40%-50% may occur in ocular and adnexal structures. Cyclooxygenase (COX)-2 is an inducible enzyme responsible for the production of prostaglandins that control cell growth and the development and progression of cancer. Mechanisms responsible for the initial upregulation of COX-2 in neoplasia are unclear; prolonged sunlight exposure and mutations in the p53 gene may be possibilities. Because the etiopathogenesis of ocular SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Another group reported that a small percentage (<10%) of neoplastic cells from 27% of corneal SCCs were only weakly positive. 95 In agreement with this observation, Smith et al 110 recently reported that less than 1% of the neoplastic cells from SCCs originating from the corneoscleral limbus, the third eyelid, and the eyelids were positive for COX-2. Finally, a study reported that the majority (32/37) of SCCs (eye/periocular, prepuce/penis, vulva) were positive for COX-2, with 56% of them having moderate to strong staining, but there was no mention of the localization in the eye and the number of ocular tumors that were positive.…”
supporting
confidence: 55%
“…Another group reported that a small percentage (<10%) of neoplastic cells from 27% of corneal SCCs were only weakly positive. 95 In agreement with this observation, Smith et al 110 recently reported that less than 1% of the neoplastic cells from SCCs originating from the corneoscleral limbus, the third eyelid, and the eyelids were positive for COX-2. Finally, a study reported that the majority (32/37) of SCCs (eye/periocular, prepuce/penis, vulva) were positive for COX-2, with 56% of them having moderate to strong staining, but there was no mention of the localization in the eye and the number of ocular tumors that were positive.…”
supporting
confidence: 55%
“…Our case showed a weak and focal immunoreactivity to COX-2 in less than 10% of neoplastic cells and was considered as a non-COX-2-overexpressing tumor [22,[38][39][40]. Previous studies have described COX-2 expression in SCC of the cornea in horses [23,24]. Since the methodologies, as well as the scoring methods, adopted are different, it is still unclear whether COX-2 plays a role in the development and progression of this type of corneal tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Since the etiopathogenesis of ocular SCC is still unclear, some authors have evaluated the expression of COX, especially COX-2, in corneal neoplastic tissues of horses and have suggested a possible role of the enzyme in oncogenesis and/or progression of this type of corneal tumor [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cycloxygenases are a family of enzymes responsible for conversion of arachidonic acid to prostaglandins and multiple isoforms of COX exist, with COX-1 and COX-2 being the most biologically active (Rassnick and Njaa 2007). Cycloxygenases are a family of enzymes responsible for conversion of arachidonic acid to prostaglandins and multiple isoforms of COX exist, with COX-1 and COX-2 being the most biologically active (Rassnick and Njaa 2007).…”
Section: Squamous Cell Carcinoma (Scc)mentioning
confidence: 99%